An Anonymous Lutheran? Can Luther's Theology Permit Salvation Outside the Church?. (2nd September 2013) - Mann, Jeffrey
Abstract: How accurate must one's religious beliefs be in order to qualify for saving faith? Is there salvation outside the visible church? How much room for error does God allow? For two millennia, Christians have struggled with these questions. Martin Luther insisted on a very precise understanding of the gospel for the reception of God's grace, leaving the vast majority of humanity without any possibility of entering the kingdom of heaven. This obviously has troubled a great many of his theological progeny. While his theology appears to demand such narrow parameters for the faithful, the author maintains that it is possible to retain Lutheran orthodoxy and posit salvation outside the visible church.